Monitoring fundamental rights in the EU : the contribution of the fundamental rights agency - Alston, Philip; De Schutter, Olivier (Oxford, 2005)
"Coherent laws enforced by a central authority are part of the reason why human rights protection works at the national level in Europe. But when it comes to the EU these dimensions are lacking. The present system for protecting fundamental rights emerged on an ad hoc basis, with measures being improvised to respond to particular problems. In the next couple of years, however, this situation is likely to change very significantly. The proposed European Constitution incorporates the EU Charter of Fundamental Rights, and a specialized EU Fundamental Rights Agency is likely to be established. As a result, the situation of the EU will more closely resemble that of its Member States. Fundamental rights will occupy a central role, and coherent and systematic arrangements will be in place to protect rights, using both judical and non-judicial means. The Fundamental Rights Agency, in particular, has immense potential to ensure effective monitoring of fundamental rights in the EU, and to ensure a unified strategy for their promotion in EU law and policy. This volume is the first to critically examine the proposals put forward by the European Commission in October 2004 on the creation of the EU Fundamental Rights Agency. Leading scholars in the field of European and international human rights law analyse the potential significance of this innovative Agency, and seek to locate it in relation to various other human rights mechanisms, both in the EU's constitutional structure and within Member States. They review the tasks which the Agency could be called upon to perform, and make proposals as to how it can function most effectively. The relationship of EU law to the international law of human rights emerging from both the United Nations and the Council of Europe is examined. The authors also address the challenge of ensuring improved coherence between EU law and the other human rights obligations undertaken by the Member States. Taken together, these contributions address urgent questions facing the EU at a time when the central unifying function of fundamental rights has been recognized but the way forward remains largely uncharted."